Training and standardization of simulated patients for multicentre studies in clinical pharmacy education - Karina A. Resende; Afonso M. Cavaco; Márcia A. Luna-Leite; Bianca R. Acacio; Núbia N. Pinto; Maria D. Neta; Angelita C. Melo (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Objective: To evaluate the training and standardization methods of multiple simulated patients (SPs) performing a single scenario in a multicenter study. Methods: A prospective quasi-experimental study, using a multicenter approach, evaluated the performance of five different individuals with the same biotype during a simulation session in a high-fidelity environment. The SPs training and standardization process consisted of four steps and six web or face-to-face mediated: Step 1: simulation scenario design and pilot test. Step 2: SPs selection, recruitment and beginning training (Session 1: performance instructions and memorization request.) Session 2: check the SPs' performances and adjustments). Step 3 and session 3: training role-play and performance's evaluation. Step 4: SPs' standardization and performances' evaluation (Sessions 4 and 5: first and second rounds of SPs' standardization assessment. Session 6: Global training and standardization evaluation. SPs performance consistency was estimated using Cronbach's alpha and ICC. Results: In the evaluation of training results, the Maastricht Simulated Patient Assessment dimensions of SPs performances "It seems authentic", "Can be a real patient" and "Answered questions naturally", presented "moderate or complete agreement" of all evaluators. The dimensions "Seems to retain information unnecessarily", "Remains in his/her role all the time", "Challenges/tests the student", and "Simulates physical complaints in an unrealistic way" presented "moderate or complete disagreement" in all evaluations. The SPs "Appearance fits the role" showed "moderate or complete agreement" in most evaluations. In the second round of evaluations, the SPs had better performance than the first ones. This could indicate the training process's had good influence on SPs performances. The Cronbach's alpha in the second assessment was better than the first (varied from 0.699 to 0.978). The same improvement occurred in the second round of intraclass correlation coefficient that was between 0.424 and 0.978. The SPs were satisfied with the training method and standardization process. They could perceive improvement on their role-play authenticity. Conclusions: The SPs training and standardization process revealed good SPs reliability and simulation reproducibility, demonstrating to be a feasible method for SPs standardization in multicenter studies. The Maastricht Simulated Patient Assessment was regarded as missing the assessment of the information consistency between the simulation script and the SPs provision.